Clinical and echocardiographic characteristics of patients in sinus rhythm, normal left ventricular function, and indeterminate diastolic function. Issue 6 (19th February 2018) - Shimron, Matan; Williams, Lynne; Hazanov, Yevgeni; Ghanim, Diab; Kinany, Wadia; Amir, Offer; Carasso, Shemy
Abstract : Background: Diastolic dysfunction (DDFx) is the major underlying mechanism of heart failure with preserved left ventricular ejection fraction (EF). Yet, the echocardiographic diagnosis of DDFx in patients in sinus rhythm is challenging and up to 25% of studies have discrepant measures making assessment of DDFx indeterminate. We aimed to describe the clinical and echocardiographic characteristics of patients with indeterminate diastolic function compared to patients with definite normal and abnormal diastolic function. Methods: One thousand six hundred seventy‐four patients were identified from the echocardiography database in sinus rhythm, EF ≥ 45% without wall‐motion abnormalities, valvular, congenital heart diseases, cardiomyopathies or pulmonary disease. Patients were divided according to their lateral mitral E/Eʹ ratio and left atrial systolic diameter: normal diastolic function (DFx) (left atrial systolic diameter [LASd] <40 mm, E/Eʹ < 10), DDFx (LASd ≥ 40 mm, E/Eʹ ≥ 10) and indeterminate DFx (discrepant LASd diameter and E/Eʹ ratio). Results: Clinical and echocardiographic characteristics of the 3 groups, DDFx (n = 186), indeterminate diastolic function (IndtDFx) (n = 207), and normal diastolic function (NDFx) (n = 1281) were significantly different. IndtDFx demonstrated intermediate parameter abnormalities, largely overlapping with DDFx. LASd and E/Eʹ were similarly associated with the inability to determine diastolic function. Age, female gender, renal failure, E/Eʹ and pulmonary pressure were found to be independent predictors of heart failure symptoms (RR = 1.02, 1.5, 2.5, 1.1, 1.1, respectively, P < .0001, r = .35). Conclusion: Clinically and echocardiographically patients with IndtDFx are more closely related to DDfx than to NDFx. Although LAd was abnormal in IndtDFx it was not predictive of heart failure symptoms. Further study is suggested to establish whether LA function rather than its maximal size can provide additional information.